Uji Efektifitas Herbisida Atrazin, Mesotrion, dan Campuran Atrazin+Mesotrion terhadap Beberapa Jenis Gulma - Nana Ratna Wati; Dad Resiworo J. Sembodo; Herry Susanto (Jurnal Penelitian Pertanian Terapan, 2015)
The aimed of this research was to know the effectiveness of mixing herbicides with active ingredient atrazin and mesotrion in controlling weeds and know the mixture characteristic. This research conducted in the plastic garden house private in Natar, South Lampung and in the Weeds laboratory of Agriculture faculty, Lampung University from June until July 2013. This Research arranged in a Randomized Completely Design (RCD). Treatment consists of three types of herbicides with six level of dosage active ingredient, namely of single herbicides is atrazin 500 g l-1 (0, 76, 152, 304, 608, and 1.215 ha g-1), mesotrion 50 g l-1 (0, 11, 22, 43, 86, and 172 g ha-1), and mixed herbicides from atrazin 500 g l-1 + mesotrion 50 g l-1 (0, 28, 56, 112, 225, and 450 g ha-1). The target weed were a type of broadleaves (Asystasia gangetica), a type of grasses (Paspalum conjugatum), and a type of sedges (Cyperus kyllingia).Homogenity tested using Bartlet and aditivity tested using Tukey, data analyzed by Analisis of Variance and different median values tested with Least Significant Difference (LSD) level 5%. Results showed that an active ingredient mixture of atrazin 500 g L-1 + mesotrion 50 g L-1 has LD50 expectation value of 51,48 g ha-1 and LD50 treatment of 257,48 g ha-1 with the co-toxicity value was 0.2 (co-toxicity < 1) until mixture was antagonist. Keywords: Atrazin, mesotrion, herbicide mixture, Multiplicative Survival Model ( MSM), LD50